Quality of life after different procedures for regional control in oral cancer patients: cross‐sectional survey. (4th February 2016) - Govers, T.M.; Schreuder, W.H.; Klop, W.M.C.; Grutters, J.P.C.; Rovers, M.M.; Merkx, M.A.W.; Takes, R.P.
Abstract : Objectives: To examine health utilities in patients with cT1‐2 oral cavity squamous cell carcinoma following different diagnostic and treatment modalities for the neck and to investigate the relation between shoulder morbidity and health utility. Design: Cross‐sectional survey. Setting: Two Dutch hospitals. Participants: Four subgroups of patients with oral cavity cancer who underwent watchful waiting, sentinel lymph node biopsy, elective supraomohyoid neck dissection or therapeutic modified radical neck dissection. Main outcome measures: Patients received the EuroQol‐5D‐3L questionnaire and the shoulder disability questionnaire. Mean health utility, visual analogue scale and shoulder disability scores were calculated. Results: A total of 181 patients (62%) returned the questionnaires. Mean health utilities, adjusted for age, gender and time since treatment were 0.804, 0.863, 0.834 and 0.794 for the watchful waiting, sentinel lymph node biopsy, supraomohyoid neck dissection and modified radical neck dissection subgroups, respectively. Mean shoulder disability scores (higher score means more shoulder complaints) for these subgroups were 8.64, 10.57, 18.92 and 33.66. Patients with shoulder complaints had a mean utility of 0.78 while patients without shoulder complaints had a mean utility of 0.90. Conclusions: This study shows that more invasive procedures appear to result in lower health utility. The high health utility for patients after sentinel lymph node biopsy supports a role for this procedure in patients with oral cancer.